New Insights on Gamma Rays - Maghraby, Ahmed M. (IntechOpen, 2017)
Gamma radiation has been discovered since more than a century and contributed in many achievements in human life. Continuous developments make it necessary to have more understandings and more discussions about well-established concepts as well as newly implemented hypothesis and applications of gamma rays. This book presents new visions of gamma ray spectrometry and applications. I hope this book can present part of the useful applications of gamma rays.